The Application of “My Pedagogic Creed” from Experiential Learning Perspective - Dr. Muhammad Asim; Nancy Joseph Lobo (Journal of Education and Educational Development, 2020)
This research measured the efficacy of experiential learning model proposed in “My Pedagogic Creed” by John Dewey in the perspective of teachers in the local context of Karachi, Pakistan. Literature reported that Dewey had promoted the notion of social interaction, group learning and experiential learning as strategies of teaching in the modern system of education. A survey questionnaire was developed and classified under four sections from experiential learning perspective: Aims and Objectives, Social Context of Teaching, Pedagogy and Teacher’s Behavior; hundred and seventy-one teachers participated in this survey. Results showed no significant difference in opinion of gender related to the above mentioned four variables. However, there was a significant difference in the opinion of male and female teachers with reference to their highest qualification and work experience regarding the said four variables. This study recommended more training for teachers in Karachi related to experiential learning model to improve the current scenario.
Keywords: Experiential Learning, Social Interaction, Group Learning, Deweyism, My Pedagogic Creed; Experiential Learning; Social Interaction; Group Learning; Deweyism; My Pedagogic Creed